Dampak Tanggung Jawab Sosial Perusahaan untuk Pengentasan Kemiskinan dan Penyediaan Layanan Umum: Studi Kasus Kabupaten Sukabumi, Indonesia - Mulus Wijaya Kusuma (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2022)
Corporate social responsibility (CSR) phenomena in developing countries are different from that of developed countries in terms of governments’ intermediary roles in the delivery mechanisms of CSR activities, especially for overcoming poverty and poor public services. By extracting Polanyi’s general principles of behavior regarding resource allocation, the distinctive CSR phenomenon in developing countries could be explained by the concept of quasi-redistribution. Considering the common character of quasi-redistribution due to its weak government system, the intermediary roles of the governments in Indonesia are noticeable due to the issuance of regulations at national and local governmental levels directing companies’ CSR activities to address poverty and poor basic public service issues. In the case of Sukabumi Regency, where the poverty and poor basic public services are the main issues, the actual role of local government in promoting company contributions to address these issues through CSR activities to alleviate poverty and provide public services is indeed increasing and developing. This paper illuminates how the intermediary roles of governments exist in CSR activities so that they alleviate poverty and provide basic public services.